Solutions for contact lenses

By treating the contact lenses with a solution of specific compound Q, the problem of insufficient hydrophilicity and antifouling of the surface is solved, and long-lasting antifouling and hydrophilicity is achieved, improving wear comfort and field of view clarity.

CN119895319APending Publication Date: 2025-04-25NOF CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380066646.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-09-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The surface hydrophilicity and antifouling properties of existing contact lenses are insufficient, resulting in discomfort in wearing and reduced visual field clarity.

Method used

A solution containing a specific compound Q, represented by formula (a), is used to impart long-lasting antifouling and hydrophilicity to the surface of the contact lens.

Benefits of technology

Through simple treatment, the solution can significantly improve the antifouling and hydrophilicity of the contact lens surface, and improve wear comfort and field of view clarity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005314558530000021
    Figure BDA0005314558530000021
  • Figure BDA0005314558530000031
    Figure BDA0005314558530000031
  • Figure BDA0005314558530000131
    Figure BDA0005314558530000131
Patent Text Reader

Abstract

The present invention provides a solution for a soft contact lens, which imparts surface hydrophilicity and antifouling properties to a soft contact lens by using a solution containing a compound Q represented by formula (a).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solution for contact lenses, which imparts hydrophilicity (particularly, permanent surface hydrophilicity) and antifouling properties (particularly, permanent antifouling properties) to the contact lens surface. Background Art

[0002] Due to the convenience of contact lenses in correcting vision, the number of wearers increases year by year, and contact lenses have become a common medical device in modern times. However, many contact lens wearers give up using contact lenses due to discomfort, and improving the comfort of wearing contact lenses remains a major challenge.

[0003] The discomfort of wearing contact lenses is often described as a "scratching feeling" and is known to be caused by reduced surface wettability of the contact lenses or adhesion of dirt when the contact lenses are worn. In addition, adhesion of dirt, especially lipid dirt, causes turbidity in the contact lenses, thereby significantly reducing the clarity of the visual field. Therefore, in order to increase the comfort of wearing contact lenses, it is important to improve the surface wettability (improvement of hydrophilicity) and antifouling properties of the contact lenses.

[0004] In order to solve the above problems, various methods have been proposed. For example, Patent Document 1 discloses a method for imparting hydrophilicity and antifouling properties to the surface of a contact lens by graft-polymerizing a hydrophilic monomer into the surface of a contact lens that has been subjected to plasma treatment. Patent Document 2 discloses a method for imparting hydrophilicity and antifouling properties to a contact lens by treating the contact lens with a solution containing hyaluronic acid having a specific molecular weight. However, in Patent Document 1, complicated steps are required, and in Patent Document 2, no attention is paid to the durability of the effect.

[0005] Patent Document 3 discloses a method for cleaning lipids and preventing lipid deposition using a composition containing a nonionic polyether surfactant having an HLB of less than 12. However, this method focuses on cleaning without considering lipid deposition (lipid adhesion).

[0006] Prior art documents

[0007] Patent Literature

[0008] Patent Document 1: JP2018-022174A

[0009] Patent Document 2: WO2013 / 031020

[0010] Patent Document 3: JP2007-513242T Summary of the invention

[0011] The purpose to be achieved by the present invention

[0012] An object of the present invention is to provide a solution for soft contact lenses which imparts hydrophilicity and antifouling properties to the surface of soft contact lenses.

[0013] Solutions to the problem

[0014] As a result of intensive studies to solve the above problems, the inventors of the present invention have found that the above problems can be solved by using a solution containing a compound Q represented by the following formula (a). Thus, the present invention has been completed.

[0015] 1. A solution for contact lenses, comprising: a compound Q represented by the following formula (a):

[0016] [Chemical formula 1]

[0017]

[0018] [In formula (a), R 1 and R 2 each represents an alkyl group having 4 to 15 carbon atoms, and A represents COO or O, and n represents 30 to 300].

[0019] 2. The solution for contact lenses according to item 1 above, wherein the solution for contact lenses is a factory solution for contact lenses.

[0020] 3. The solution for contact lenses according to 1 or 2 above, wherein R 1 and R 2 Each represents an alkyl group having 11 carbon atoms, A represents COO, and n represents 50 to 200.

[0021] Effects of the Invention

[0022] The solution for contact lenses according to the present invention can impart durable antifouling and hydrophilic properties to the surface of contact lenses through simple treatment. DETAILED DESCRIPTION

[0023] <Solutions for contact lenses>

[0024] The solution for contact lenses according to the present invention is a solution for contact lenses comprising a compound Q represented by the following formula (a) as an effective component (main component).

[0025] [Chemical formula 2]

[0026]

[0027] [In formula (a), R 1 and R 2 Each represents an alkyl group having 4 to 15 carbon atoms, and A represents COO or O. n represents 30 to 300.]

[0028] In this specification, when describing a preferred numerical range (e.g., concentration range) in stages, each lower limit and upper limit can be independently combined. For example, in the description of "preferably 10 or more, more preferably 20 or more, and preferably 100 or less, more preferably 90 or less", "preferable lower limit: 10" and "more preferably upper limit: 90" can be combined as "10 or more and 90 or less". In addition, for example, the description of "preferably 10 to 100, more preferably 20 to 90" can also be combined as "10 to 90" in the same way.

[0029] In formula (a), n (average addition mole number of oxyethylene groups) is 30 to 300, preferably 30 to 250, more preferably 50 to 200, and still more preferably 60 to 100. When n is less than 30, it is difficult to prepare a solution, and the expected effect cannot be obtained.

[0030] Furthermore, when n is greater than 300, there is a problem that sterilization by filtration is difficult.

[0031] In formula (a), R 1 and R 2 Each represents an alkyl group having 4 to 15 carbon atoms, preferably an alkyl group having 5 to 15 carbon atoms, and more preferably an alkyl group having 8 to 12 carbon atoms. When the number of carbon atoms is greater than 15, hydrophobicity increases, and thus there is a concern that the effect of improving antifouling properties is impaired. In addition, when the number of carbon atoms is less than 3, there is a problem that adhesion to a contact lens may be weakened.

[0032] In formula (a), A is ester (COO) or ether (O), preferably ester (COO).

[0033] Examples of compound Q include polyethylene glycol dilaurate (R 1 and R 2 each being an alkyl group having 11 carbon atoms, and A being COO), polyethylene glycol dipalmitate (R 1 and R 2 each being an alkyl group having 15 carbon atoms, and A being COO), and polyoxyethylene myristyl ether myristate (R 1 is an alkyl group having 14 carbon atoms, R 2 is an alkyl group having 13 carbon atoms, and A is O). Polyethylene glycol dilaurate is preferred.

[0034] The mixing amount of compound Q in the solution for contact lens according to the present invention is not particularly limited and is preferably within the range of 0.0001 w / v% to 0.3 w / v%, more preferably 0.001 w / v% to 0.2 w / v% and still more preferably 0.01 w / v% to 0.1 w / v%.

[0035] When the content is less than 0.0001 w / v%, there is a possibility that sufficient effects cannot be obtained, and when the content is more than 0.3 w / v%, there is a possibility that handling becomes difficult due to increased viscosity and foaming when manufacturing a solution for contact lenses.

[0036] <Additives>

[0037] The solution for contact lenses according to the present invention may contain, in addition to compound Q as a main component (effective component), additives and the like for preparing ordinary solutions for contact lenses, if necessary.

[0038] The mixing amount of the additive is not particularly limited, and is preferably 0.01 w / v% to 5.0 w / v%, more preferably 0.05 w / v% to 4.0 w / v%, and still more preferably 0.1 w / v% to 3.0 w / v%.

[0039] Examples of additives include vitamins, thickeners, amino acids, sugars, coolants, inorganic salts, organic acid salts, antioxidants, stabilizers, preservatives, chelating agents, buffers, and the like.

[0040] Examples of vitamins include sodium flavin adenine dinucleotide, cyanocobalamin, retinyl acetate, retinyl palmitate, pyridoxine hydrochloride, panthenol, sodium pantothenate, and calcium pantothenate.

[0041] Examples of thickeners include hydroxypropyl methylcellulose, polyvinyl alcohol, sodium hyaluronate, alginic acid, guar gum, cellulose and its derivatives.

[0042] Examples of amino acids include aspartic acid and salts thereof, and aminoethylsulfonic acid.

[0043] Examples of sugars include glucose, mannitol, sorbitol, xylitol, and trehalose.

[0044] Examples of coolants include menthol and camphor.

[0045] Examples of inorganic salts include sodium chloride and potassium chloride.

[0046] Examples of organic acid salts include sodium citrate.

[0047] Examples of antioxidants include tocopherol acetate, taurine, sodium bisulfite, sodium sulfite, and butylated hydroxytoluene.

[0048] Examples of stabilizers include sodium edetate and glycine.

[0049] Examples of preservatives include benzalkonium chloride, chlorhexidine gluconate, potassium sorbate, polyhexanide hydrochloride, parabens, and chlorobutanol.

[0050] Examples of the chelating agent include EDTA-2Na, tris(hydroxymethyl)aminomethane, and sodium hexametaphosphate.

[0051] Examples of buffers include borate buffer, phosphate buffer and citrate buffer. In addition, phosphate buffer is a buffer containing a component selected from disodium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate and hydrates thereof, as well as hydrochloric acid, sodium hydroxide and potassium hydroxide. Borate buffer is a buffer containing a component selected from boric acid, borax, hydrochloric acid, sodium hydroxide and potassium hydroxide.

[0052] <Method for preparing a solution for contact lenses>

[0053] The solution for contact lenses according to the present invention can be prepared by using a general method for preparing a solution for contact lenses, wherein compound Q as a main component, water and other components (additives) are mixed and stirred, if necessary. In the preparation process, heating and stirring steps may be added according to the solubility of other components added. Note that the obtained solution for contact lenses may be subjected to operations such as sterilization filtration, if necessary.

[0054] <pH of the solution for contact lenses>

[0055] The solution for contact lenses according to the present invention has a pH of preferably 3 to 9, more preferably 3 to 8, and still more preferably 4 to 8, from the viewpoint of improving the comfort of wearing the contact lenses.

[0056] Note that the pH of the solution for contact lenses in the present specification refers to a value measured according to the pH determination of General Test Methods 2.54 in the Eighteenth Edition of the Japanese Pharmacopoeia.

[0057] <Osmotic Pressure and Osmotic Pressure Ratio of Solutions for Contact Lenses>

[0058] From the viewpoint of improving the comfort of wearing contact lenses, the solution for contact lenses according to the present invention has an osmotic pressure of preferably 200 to 400 mOsm, more preferably 210 to 350 mOsm, and still more preferably 220 to 340 mOsm, and has an osmotic pressure ratio of preferably 0.7 to 1.4, more preferably 0.8 to 1.3, and still more preferably 0.8 to 1.2.

[0059] Note that the osmotic pressure of the solution for contact lenses in this specification refers to a value measured according to the osmotic pressure determination (osmotic pressure molar concentration determination) of General Test Methods 2.47 in the Eighteenth Edition of the Japanese Pharmacopoeia, and the osmotic pressure ratio refers to a value obtained by dividing the obtained osmotic pressure value by the osmotic pressure value (286 mOsm) of 0.9 mass % physiological saline.

[0060] <Product form of solution for contact lenses>

[0061] Specific examples of the product form of the solution for contact lenses according to the present invention include factory solution for contact lenses, contact lens care products, disinfectants for contact lenses, solutions for storing contact lenses, solutions for cleaning contact lenses, solutions for cleaning and storing contact lenses, solutions for disinfecting, cleaning and storing contact lenses, and contact lens wearing solutions.

[0062] When the solution is used as a factory solution for contact lenses, the contact lenses can be immersed in the solution for contact lenses according to the present invention, sealed, and then heat-sterilized.

[0063] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited thereto.

[0064] [Example 1-1]

[0065] About 80 g of purified water was weighed, and 0.005 g of polyethylene glycol dilaurate (average addition mole number of ethylene oxide groups: 70), 0.83 g of sodium chloride, 0.053 g of sodium dihydrogen phosphate dihydrate, and 0.599 g of disodium hydrogen phosphate dodecahydrate were weighed and dissolved therein. Thereafter, purified water was added so that the total volume was 100 mL. Filtration sterilization was performed to obtain a sterile solution for contact lenses according to the present invention (particularly, a factory solution for contact lenses). The solution for contact lenses thus obtained was evaluated for the effect of improving the hydrophilicity of the contact lenses and the effect of improving the antifouling property of the contact lenses, which will be described later. The results are shown in Table 1.

[0066] [Example 1-2 to Example 1-4 and Comparative Example 1-1 to Comparative Example 1-4]

[0067] A sterile solution for contact lens (particularly, a factory solution for contact lens) was prepared by the same process as in Example 1, except that the types and amounts shown in Table 1 or Table 2 were used. Each of the solutions for contact lenses thus obtained was evaluated for the effect of improving the hydrophilicity of the contact lens and the effect of improving the antifouling property of the contact lens, which will be described later. The results are shown in Tables 1 and 2.

[0068] [Example 2-1 to Example 2-4 and Comparative Example 2-1 to Comparative Example 2-4]

[0069] According to the formulation examples shown in Tables 3 and 4, solutions for contact lenses (particularly contact lens care products) according to the present invention were prepared. Contact lens care products were prepared in the same manner as in Example 1-1, except that the types and amounts shown in Tables 3 and 4 were used. Each contact lens care product was evaluated for its effect of improving the hydrophilicity of the contact lens and its effect of improving the antifouling property of the contact lens, which will be described later. The results are shown in Tables 3 and 4.

[0070] <Examination of the effect of improving the hydrophilicity of contact lenses>

[0071] In Examples and Comparative Examples, the hydrophilicity of the contact lenses was evaluated according to the following procedure: Note that, in order to examine the effect of improving the hydrophilicity of the contact lenses, Polymacon (nonionic low water content material) lenses were used.

[0072] (process)

[0073] 1) The solution for contact lenses in Examples or Comparative Examples was used.

[0074] 2) Place one contact lens into a 15 mL centrifuge tube.

[0075] 3) Add 10 mL of physiological saline solution to the centrifuge tube in 2) and shake overnight.

[0076] 4) Remove the physiological saline solution from the centrifuge tube in 3), and add 10 mL of the solution for contact lenses in 1) to the centrifuge tube.

[0077] 5) The centrifuge tube in 4) was sterilized by autoclaving at 121° C. for 20 minutes. However, this operation was not performed in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-4.

[0078] 6) After cooling to room temperature, the contact lens was taken out, and the time until the water film on the lens surface disappeared (BUT) was measured with a stopwatch. Those with a BUT of 10 seconds or more were evaluated as having "excellent surface hydrophilicity" and marked with "B" in Table 1, and those with a BUT of 15 seconds or more were evaluated as having "particularly excellent surface hydrophilicity" and marked with "A", and those with a BUT shorter than 10 seconds were marked with "C" in Tables 1 to 4.

[0079] <Evaluation of Durability of the Effect of Improving the Hydrophilicity of Contact Lenses>

[0080] (process)

[0081] 1) The solution for contact lenses in Examples or Comparative Examples was used.

[0082] 2) Place one contact lens into a 15 mL centrifuge tube.

[0083] 3) Add 10 mL of physiological saline solution to the centrifuge tube in 2) and shake overnight.

[0084] 4) Remove the physiological saline solution from the centrifuge tube in 3), and add 10 mL of the solution for contact lenses in 1) to the centrifuge tube.

[0085] 5) The centrifuge tube in 4) was sterilized by autoclaving at 121° C. for 20 minutes. However, this operation was not performed in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-4.

[0086] 6) After cooling to room temperature, the contact lens was taken out, and then the contact lens was immersed in 2 mL of physiological saline solution and washed with shaking for 30 minutes.

[0087] 7) The remaining operations and evaluations were performed in the same manner as in <Examination of the effect of improving the hydrophilicity of contact lenses>. The evaluation results are shown in Tables 1 to 4.

[0088] <Evaluation of the effect of improving the antifouling properties of contact lenses>

[0089] In Examples and Comparative Examples, the antifouling property of the contact lens was evaluated according to the following procedure. Note that, in order to examine the effect of improving the antifouling property of the contact lens, ACUVUEOASYS (registered trademark) (manufactured by Johnson & Johnson) was used.

[0090] (process)

[0091] Preparation of artificial eye fat

[0092] 1) 0.5 g of the lipid mixture having the following composition was mixed with 100 mL of the following phosphate-borate buffer.

[0093] 2) The mixture was suspended at 60°C using a homomixer.

[0094] 3) The pH was adjusted to 7.0 with 1N hydrochloric acid.

[0095] ○Composition of lipid mixture

[0096] Oleic acid: 0.06g

[0097] Linolenic acid: 0.06g

[0098] Palmitic acid: 0.06g

[0099] Tripalmitic acid: 0.81g

[0100] Cetyl alcohol: 0.20g

[0101] Cetyl myristate: 0.81g

[0102] Cholesterol: 0.08g

[0103] Cholesterol palmitate: 0.08g

[0104] Lecithin (from eggs): 2.83 g

[0105] ○Composition of phosphate-borate buffer

[0106] Sodium chloride: 2.25 g

[0107] Potassium dihydrogen phosphate: 1.25g

[0108] Sodium tetraborate decahydrate: 5.65g

[0109] Ion exchange water: total volume 250mL

[0110] (evaluate)

[0111] 1) The solution for contact lenses in Examples or Comparative Examples was used.

[0112] 2) Place one contact lens into a 15 mL centrifuge tube.

[0113] 3) Add 10 mL of physiological saline solution to the centrifuge tube in 2) and shake overnight.

[0114] 4) Thereafter, the physiological saline solution was removed, and 10 mL of the solution for contact lenses in 1) was added to the centrifuge tube in 3).

[0115] 5) Autoclave sterilization was performed at 121° C. for 20 minutes. However, this operation was not performed in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-4.

[0116] 6) After the contact lenses were cooled to room temperature, one contact lens was immersed in 4 mL of artificial eye fat for 4 hours.

[0117] 7) Remove the contact lens, rinse gently with saline solution, and dry.

[0118] 8) Immerse the contact lens in 3 mL of extraction solution (ethanol / ether = 1 / 1 (v / v)).

[0119] 9) Perform ultrasonic treatment for 10 minutes.

[0120] 10) The amount of lipid in the extract was quantified by using the vanillin-phosphoric acid method (see Ii Kaorau, Moriyama Mari, Imayasu Masaki, Tanaka Hidenari: Study on lipid adhesion to contact lenses, Journal of Japan Contact Lens Society, vol. 37, pp. 58-61, 1995).

[0121] The amount of lipid adhered to the contact lens was determined by comparing the obtained absorbance with the calibration curve. A similar test was performed using a physiological saline solution as a solution for contact lenses, and the lipid adhesion inhibition rate was calculated based on the measured lipid adhesion amount. The case where the lipid adhesion inhibition rate was 25% or more was evaluated as "having adhesion inhibition power", and the case where the lipid adhesion inhibition rate was 50% or more was evaluated as "having particularly excellent adhesion inhibition power". The evaluation results are shown in Tables 1 to 4.

[0122] <Evaluation of Durability of the Effect of Improving Antifouling Properties of Contact Lenses>

[0123] (process)

[0124] 1) The solution for contact lenses in Examples or Comparative Examples was used.

[0125] 2) Place one contact lens into a 15 mL centrifuge tube.

[0126] 3) Add 10 mL of physiological saline solution to the centrifuge tube in 2) and shake overnight.

[0127] 4) Thereafter, the physiological saline solution was removed, and 10 mL of the solution for contact lenses in 1) was added to the centrifuge tube in 3).

[0128] 5) Autoclave sterilization was performed at 121° C. for 20 minutes. However, this operation was not performed in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-4.

[0129] 6) After the contact lens was cooled to room temperature, the contact lens was taken out, and then the contact lens was immersed in 2 mL of physiological saline solution and washed with shaking for 30 minutes.

[0130] 7) Immerse a contact lens in 4 mL of artificial eye fat for 4 hours.

[0131] 8) Remove the contact lens, rinse gently with saline solution, and dry.

[0132] 9) Immerse the contact lens in 3 mL of extraction solution (ethanol / ether = 1 / 1 (v / v)).

[0133] 10) Perform ultrasonic treatment for 10 minutes.

[0134] 11) The amount of lipid in the extract was quantified by using the vanillin-phosphoric acid method.

[0135] Based on the obtained absorbance, the lipid adhesion inhibition rate was calculated in the same manner as in <Evaluation of the effect of improving the antifouling property of contact lenses>. The evaluation results are shown in Tables 1 to 4.

[0136] [Table 1]

[0137]

[0138] [Table 2]

[0139]

[0140] * In the evaluation of antifouling properties, - (minus sign) indicates that the adhesion amount is greater than that of a physiological saline solution.

[0141] [Table 3]

[0142]

[0143] EO: Average number of moles of ethylene oxide added

[0144] [Table 4]

[0145]

[0146] * In the evaluation of antifouling properties, - (minus sign) indicates that the adhesion amount is greater than that of a physiological saline solution.

[0147] <Evaluation Results>

[0148] ○Examples 1-1 to 1-4

[0149] The surface hydrophilicity of the contact lens is particularly excellent. In addition, the permanent surface hydrophilicity is particularly excellent or excellent.

[0150] In terms of the antifouling property of the contact lens, the adhesion inhibition power is particularly excellent or excellent. In addition, similarly, in terms of the long-term antifouling property of the contact lens, the adhesion inhibition power is particularly excellent or excellent.

[0151] As shown by the results in Example 1-1 and Example 1-3, polyethylene glycol dilaurate (EO: about 70) as the main component of the solution for contact lenses according to the present invention is more excellent than polyethylene glycol dilaurate (EO: about 150).

[0152] It can be seen that the solution for contact lenses according to the present invention also has excellent effects as a factory solution for contact lenses.

[0153] ○Examples 2-1 to 2-4

[0154] The surface hydrophilicity of the contact lens is particularly excellent. In addition, the permanent surface hydrophilicity is particularly excellent or excellent.

[0155] In terms of the antifouling property of the contact lens, the adhesion inhibition power is particularly excellent. In addition, similarly, in terms of the long-term antifouling property of the contact lens, the adhesion inhibition power is particularly excellent.

[0156] It can be seen that the solution for contact lenses according to the present invention also has excellent effects as a contact lens care product.

[0157] ○Comparative Examples 1-1 to 1-4

[0158] Since Comparative Example 1-2 was insoluble, it was not evaluated.

[0159] Regarding Comparative Examples 1-1, 1-3, and 1-4, no effect was obtained in any of the surface hydrophilicity, the lasting surface hydrophilicity, the antifouling property, and the lasting antifouling property.

[0160] ○Comparative Examples 2-1 to 2-4

[0161] Since Comparative Example 2-2 was insoluble, it was not evaluated.

[0162] It can be seen that Comparative Examples 2-1, 2-3, and 2-4 do not have durable surface hydrophilicity, antifouling properties, or durable antifouling properties.

[0163] The solution for contact lenses according to the present invention can impart durable antifouling and hydrophilicity to the surface of the contact lenses through simple treatment, and can impart good comfort and vision when the contact lenses are worn.

[0164] Industrial Applicability

[0165] A solution for contact lenses can be provided which imparts durable surface hydrophilicity and antifouling properties to the contact lenses.

[0166] Although the present invention has been described in detail and with reference to specific embodiments thereof, it will be apparent to one skilled in the art that various changes or modifications can be made to the present invention without departing from the spirit and scope of the present invention.

[0167] This application is based on the Japanese patent application filed on September 15, 2022 (Japanese patent application number 2022-146799), the contents of which are incorporated herein by reference.

Claims

1. A solution for contact lenses, characterized in that Containing a compound Q represented by the following formula (a), [Chemical formula 1] In formula (a), R 1 and R 2 Each represents an alkyl group having 4 to 15 carbon atoms, and A represents COO or O, and n represents 30 to 300.

2. The solution for contact lenses according to claim 1, wherein R 1 and R 2 Each represents an alkyl group having 11 carbon atoms, A represents COO, and n represents 50 to 200.

Citation Information

Patent Citations

  • Contact lens cleaning composition containing nonionic surfactant

    JP2007513242A

  • Vegetable harvester

    JP2022146799A